UJI EFEKTIVITAS EKSTRAK RIMPANG KUNYIT TERHADAP BAKTERI BACILLUS CEREUS DENGAN PEMBANDING CIPROFLOXACIN - Maulidi, Risyad Rizki; Pangaribuan, Novita Helshinta Dewi; Ginting, Frisdayanti Br; Sheridan, Princessa Fath; Lubis, Yolanda Eliza Putri (Universitas Jambi, 2020)
This research aims to find out effectiveness test of turmeric rhizome in concentration of 25%, 50%, 75% and 100% toward Bacillus cereus bacterial and Ciprofloxacin the same concentration as the comparison. Bacillus cereus Bacteria is a gram-positive rod-shaped bacteria and it is dangerous for humans. This research was conducted with an experimental method with post-test only design and sampling using purposive sampling method. The effectiveness test of turmeric rhizome extract toward Bacillus cereus bacteria was carried out by diffusion using disc paper by calculating the diameter of the bacterial inhibition zone against disc paper that had been moistened with turmeric rhizome extract or Ciprofloxacin solution. The results obtained in this research were carried out with the Post Hoc test, the test was found that there were significant differences from each treatment given with a 95% confidence index. In bacteria treated with 25% ciprofloxacin toward Bacillus cereus, the effectiveness was above 50% turmeric rhizome extract and under 75% turmeric extract. Turmeric extract of 75% 10.6 mm had bacterial effect as Ciprofloxacin 25% of 10.1 mm toward the growth of Bacillus cereus bacterial.